Extraction of Glucose by Supported Liquid Membrane using Polyethersulfone Flat Sheet Membrane Support - Teng, S. S.; Harruddin, N.; M. Saufi, Syed (Journal of Applied Membrane Science & Technology, 2017)
Sugar is released during biomass hydrolysis together with unwanted inhibitory compounds such as acetic acid, furfural and hydromethylfurfural. The extraction of particular sugar prior to fermentation process is needed in order to increase the yield of biofuel generated from biomass resources. In the current study, glucose was extracted from the aqueous solution using supported liquid membrane (SLM) system. Polyethersulfone (PES) flat sheet membrane support was fabricated using 15 wt.% PES, 42.5 wt.% DMAc and 42.5 wt.% PEG 200. Liquid membrane was formulated using 2-ethyl hexanol and methyl cholate as solvent and carrier, respectively. The effect of several parameters involved in SLM system such as type of diluent and flowrate of feed and stripping phase on the extraction performance of glucose were studied. About 52.77% of glucose was successfully extracted from aqueous solution using SLM system with 0.01M of methyl cholate in 2-ethyl hexanol. Using simulated biomass hydrolysate solution, almost 54.55% of glucose and 51.08% of xylose were successfully extracted using the SLM system.